Exoskeletons' design and usefulness evidence according to a systematic review of lower limb exoskeletons used for functional mobility by people with spinal cord injury. (2nd October 2016) - Lajeunesse, Veronique; Vincent, Claude; Routhier, François; Careau, Emmanuelle; Michaud, François
Abstract: Purpose : Rehabilitation professionals have little information concerning lower limb exoskeletons for people with paraplegia. This study has four objectives: (1) Outline the characteristics of the exoskeletons' design and their usefulness evidence as assistive mobility devices in the community for the Rewalk™, Mina, Indego®, Ekso™ (previously known as the eLEGS™) and Rex®; (2) document functional mobility outcomes of using these exoskeletons; (3) document secondary skills and benefits achieved with these exoskeletons, safety, user satisfaction and applicability in the community; and (4) establish level of scientific evidence of the selected studies. Method : A systematic review of the literature (January 2004 to April 2014) was done using the databases PubMed, CINAHL and Embase and groups of keywords associated with "exoskeleton", "lower limb" and "paraplegia". Results : Seven articles were selected. Exoskeleton use is effective for walking in a laboratory but there are no training protocols to modify identified outcomes over the term usage (ReWalk™: 3 months, Mina: 2 months and Indego®: 1 session). Levels of evidence of selected papers are low. Conclusions : The applicability and effectiveness of lower limb exoskeletons as assistive devices in the community have not been demonstrated. More research is needed on walking performance with these exoskeletons compared to other mobility devices and other training contexts in the community. Implications for rehabilitation: Characteristics of the exoskeletons' design and their usefulness evidence as assistive mobility devices in the community are addressed for the Rewalk™, Mina, Indego®, Ekso™ and Rex® ReWalk™, Indego® and Mina lower limb exoskeletons are effective for walking in a laboratory for individuals with complete lower-level SCI. The ReWalk™ has the best results for walking, with a maximum speed of 0.51 m/s after 45 sessions lasting 60 to 120 min; it is comparable to the average speed per day or per week in a manual wheelchair. The level of scientific evidence is low. Other studies are needed to provide more information about performance over the longer term when walking with an exoskeleton, compared to wheelchair mobility, the user's usual locomotion, the use of different exoskeletons or the training context in which the exoskeleton is used.